Label-free detection of Alzheimer's disease through the ADP3 peptoid recognizing the serum amyloid-beta42 peptide. Issue 4 (24th November 2014) - Zhao, Zijian; Zhu, Ling; Bu, Xiangli; Ma, Huailei; Yang, Shu; Yang, Yanlian; Hu, Zhiyuan
Abstract : Surface plasmon resonance imaging in combination with the ADP3 peptoid was used to identify Alzheimer's disease through detecting amyloid-beta42 in the serum. Abstract : The early diagnosis of Alzheimer's disease (AD) is challenging due to the lack of reliable methods for detecting its biomarkers in the noninvasive biopsies. We used surface plasmon resonance imaging to identify AD based on the detection of amyloid-beta42 in the serum by the ADP3 peptoid.